2018
DOI: 10.1364/oe.26.007056
|View full text |Cite
|
Sign up to set email alerts
|

Robust, tunable, and high purity triggered single photon source at room temperature using a nitrogen-vacancy defect in diamond in an open microcavity

Abstract: We report progress in the development of tunable room temperature triggered single photon sources based on single nitrogen-vacancy (NV) centres in nanodiamond coupled to open access optical micro-cavities. The feeding of fluorescence from an NV centre into the cavity mode increases the spectral density of the emission and results in an output stream of triggered single photons with spectral line width of order 1 nm, tunable in the range 640 - 700 nm. We record single photon purities exceeding 96% and estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…A custom-built confocal set-up was used to perform spectral measurement and photon correlation experiments as we previously reported. 41 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A custom-built confocal set-up was used to perform spectral measurement and photon correlation experiments as we previously reported. 41 …”
Section: Methodsmentioning
confidence: 99%
“…A custom-built confocal set-up was used to perform spectral measurement and photon correlation experiments as we previously reported. 41 For pH sensing, the 10 nm NDs were immersed in different buffer solutions using silicone gaskets to form wells. A 0.01 M HCl solution was used for pH 1.2; a 0.1 M NaOH solution for pH 12.8-12.9; a 1× phosphate-buffered saline solution (PBS) for pH 7; a commercial buffer solution (Hanna instruments) was used for pH 4 and 10.…”
Section: Microscope and Imagingmentioning
confidence: 99%
“… The open Fabry–Pérot IR microcavity used in this work consists of two Au mirrors, prepared on circular CaF 2 windows ( d = 25.0 mm, 5.0 mm thickness) by a high vacuum sputtering (Leica EM MED 020). The thickness of the Au film was controlled using a quartz crystal balance as a reference during sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…Dolan et al. demonstrated in the same type of cavity single‐photon generation, which exhibited photon purities exceeding 96% and device efficiencies up to 3% . The authors also carried out systematic studies using concave mirrors with a series of RoCs ranging from 4 to 25 µm, and concluded that RoC = 8 µm enabled the best device performance by the interplay between cavity feeding and photon extraction.…”
Section: Single‐photon Emitters and Nanoparticles In Open‐access Micrmentioning
confidence: 99%